2015
DOI: 10.7314/apjcp.2015.16.4.1605
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Ki67 in Papillary Thyroid Microcarcinoma and its Clinical Significance

Abstract: Purpose: To investigate the expression of Ki67 protein in papillary thyroid microcarcinoma(PTMC), and to analyze its clinical significance. Materials and Methods: Ki67 protein expression was evaluated in the tissues of 108 human PTMC and 50 other benign papillary hyperplasia of thyroid specimens using immunohistochemistry. Results: The expression intensity of Ki67 in PTMC and benign papillary hyperplasia of thyroid specimens were 1.45±1.83% and 0.46±0.46%.The positive expression rates were 46.3% and 14%. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
3
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 10 publications
1
22
3
4
Order By: Relevance
“…Therefore, a preoperative analysis of Ki-67 LI by fine needle aspiration may be useful for determining an appropriate PTMC management strategy in the future. It was previously reported that high Ki-67 LI in PTMC was related to nodal metastasis [20]. However, our results did not support these findings.…”
Section: Discussioncontrasting
confidence: 57%
“…Therefore, a preoperative analysis of Ki-67 LI by fine needle aspiration may be useful for determining an appropriate PTMC management strategy in the future. It was previously reported that high Ki-67 LI in PTMC was related to nodal metastasis [20]. However, our results did not support these findings.…”
Section: Discussioncontrasting
confidence: 57%
“…We have found a negative correlation between SR5 expression and ki67 percentage. Whereas high ki67 proliferation index is an important prognostic factor in many tumors (Kilickap et al,2014;Zhou et al, 2015) , it has a special importance in GN. The reason is that the percentage of ki67 proliferation index is used in grading and the determination whether to give chemotherapy in GN (Rindi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Ki67 indicates active cells during cell cycle. It is an important cell marker that shows cell proliferation and is an important prognostic factor for various malignancies (Kilickap et al,2014;Zhou et al, 2015). Additionally the percentage of ki67 proliferation is an important parameter in World Health Organization (WHO) 2010 classification of GN (Rindi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…12 Molecular markers (BRAF, PIK3CA, AKT1, TERT, TP53) may be useful in the future for prognostic stratification, especially the coexistence of these markers [13][14][15][16] as well as the expression of the Ki67 protein, which is associated with PTMC size, tumor invasion, lymph node metastasis, and may be used in the future as a monitoring and a clinical decision parameter. 17 In the group of patients with low-risk PTMC that demand surgery during the follow-up (<10% of cases), it does not impact on the outcome. Therefore, our conduct for a patient diagnosed with a PTMC and all the low-risk criteria (outlined above), such as over 40 years of age, without history of head and neck radiation, nor family history of thyroid cancer, is active surveillance.…”
mentioning
confidence: 97%